Consumer Perceptions of the Influence of Brand Image, Store Atmosphere, Promotions and Product Innovation on Coffee Purchasing Decisions - Nurul Hidayati Hafizza; Darnetti Darnetti; Roni Afrizal (Politeknik Baubau, 2026)
Consumer purchasing decisions are processes influenced by various factors before consumers decide to buy a product or service. This study aims to analyze the effect of brand image (X1), store atmosphere (X2), promotion (X3), and product innovation (X4) on consumer purchasing decisions at Cafe Ribian in Payakumbuh City. The research employs a descriptive quantitative method, with data collected through questionnaires. The sample consists of 100 respondents who are customers of Cafe Ribian, selected using a purposive sampling technique. Data analysis was conducted using multiple linear regression with IBM SPSS version 26 to examine the partial and simultaneous effects of the variables on purchasing decisions. The results indicate that brand image, store atmosphere, promotion, and product innovation have positive and significant effects on purchasing decisions, both partially and simultaneously. These findings highlight the importance of strengthening brand image, creating a comfortable store atmosphere, implementing effective promotional strategies, and continuously innovating products to enhance consumer purchasing decisions in the cafe sector.